2018
DOI: 10.5750/ejpch.v6i2.1461
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a person-centred and strength-based health intervention on recovery among people with chronic illness

Abstract: Denne filen er hentet fra Lovisenberg diakonale høgskoles institusjonelle arkiv LDH Brage.The effect of a person-centered and strength-based health intervention on recovery among people with chronic illness Abstract Background: Strengthening the health capacities of people diagnosed with a chronic illness is an essential part of secondary and tertiary prevention. However, research-based interventions focussed on health and recovery in chronic illness remain scarce. Additionally, these are often designed for sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…This applied to different areas of life, including family life, working life, and social life. These findings indicate that the BKP attends especially to the psychosocial dimensions of health in individuals with chronic illness and relational support [38,53,54]. According to Dwarswaard et al [71] relational support is at the center of the support needs and fuels all other types of support.…”
Section: Special Attention To the Psychosocial Dimensions Of Health Amentioning
confidence: 91%
See 3 more Smart Citations
“…This applied to different areas of life, including family life, working life, and social life. These findings indicate that the BKP attends especially to the psychosocial dimensions of health in individuals with chronic illness and relational support [38,53,54]. According to Dwarswaard et al [71] relational support is at the center of the support needs and fuels all other types of support.…”
Section: Special Attention To the Psychosocial Dimensions Of Health Amentioning
confidence: 91%
“…This is an essential finding, as perceived internal control is necessary in order for patients to be in charge of their own health. In another study of the efficiency of BKP in community care, the Outcome Rating Scale (ORS) was used to measure patients' self-reported recovery repeatedly at baseline, after four sessions of BKP and after program completion [54]. Four dimensions were assessed: (1) individual (personal or symptomatic distress and well-being), (2) interpersonal (relational distress or well-being), (3) social (patient satisfaction with work, school, and relationships), and (4) overall (general sense of well-being).…”
Section: Trials Of the Bkp Intervention In Community Carementioning
confidence: 99%
See 2 more Smart Citations
“…In a separate study of the feasibility and outcomes in community care, participants reported that their engagement in the intervention improved perceived control of illness‐related stress and circumstances when HCP challenged patients to get to know their bodies and utilize their knowledge of health and illness 21 . Another study investigating the efficiency of BKP in community care reported significant changes in recovery 22 . A comparative study of BKP participants in specialist and community care showed that SOC improved at programme completion in both groups 23 .…”
Section: Introductionmentioning
confidence: 99%